Data is the new oil. How Covid-19 boosted information transparency in Austria. (20th October 2021) - Habl, CA; Hummer, M; Maier, G
Abstract: Background: Austria has no tradition of sharing administrative or routine (health) data collected by public authorities with researchers and accordingly no corresponding data infrastructure exists. Triggered by the GDPR and the pandemic situation an increasing demand from scientific institutions to obtain access to health care data (e.g. use of resources, patient pathways) for research purposes emerged. The latest governmental program addressed this fundamental request even before the start of the pandemic mainly because one of the members of the current coalition, the Green Party, values information transparency very high. The abolishment of "professional secrecy" and the promotion of research by enabling a comprehensive secondary use of data are cornerstones of their political agenda. Mathods: The agenda was boosted by the outbreak of the Covid-19 pandemic that made the need for joint and real-time data-based research into SARS-CoV-2 and COVID-19 evident and eventually led to the establishment of the Covid-19 data platform https://datenplattform-covid.goeg.at in April 2020, which is run by the Austrian National Public Health Institute (GÖG). Since June 2020 national and international scientific institutions can obtain, free of cost, data from the Epidemiological reporting system which includes core information on COVID-19 infections in Austria. Institutions need to apply with GÖG for accreditation which is granted (or denied) by the Scientific Advisory Board of the Platform. Data provision is continuously expanded and includes as of now, data on hospital and ICU admissions due to COVID-19 as well as data on SARS-CoV-2 genome sequencing. Results: In April 2021, 84 institutions (8 international) had applied for access. 60 have been accredited, in line with the rules of procedure (incl. a plausibility check of the applicant against OECD's Frascati-criteria. In total, nine articles using data from the Covid-19 platform have been submitted to scientific journals. Key messages: On a national level, the Covid-19 data platform, commissioned by the Austrian Ministry of Health (BMSGPK) is an important step towards a modern and transparent health care administration system. Covid-19 and the data platform triggered a debate around the need for a (national) data-governance framework balancing benefits from data usage vs the right to data protection of citizens' health data.